Electrocatalytic reduction of simulated industrial CO2 and CO mixtures: revising chronoamperometry to enable selective gas mixture reduction via cyclic voltammetry - Chen, Wen Qian (2024)
While substantial advancements have been achieved in the electrocatalytic reduction of pure CO2 or CO, the reduction of carbon oxide mixtures remains underexplored, a key limitation in scaling the technology for industrial applications. This underexplored domain gains practical importance by considering carbon oxide mixtures, given that CO and CO2 together constitute a large proportion of diverse industrial gas streams. However, the simultaneous reduction of mixed CO and CO2 poses a potential challenge due to their differing optimal reduction potentials, which complicates an efficient reduction process. While cyclic voltammetry (CV) is typically used for characterization, which involves sweeping between positive and negative potentials, we utilized it to conduct reduction reactions within a defined negative potential window. This approach, serving as an alternative to conventional chronoamperometry that maintains a constant potential, ensures a continuous reduction reaction throughout the entire cycling process. By employing cycling between the optimized reduction potentials of CO2 (−1.4 V) and CO (−1.6 V), CV achieved an increase in production efficiency, ranging from 25 % to 40 % for predominant products (HCOOH and C2H4), in comparison to chronoamperometry. Meanwhile, the results underscored the dependency of performance enhancement on the scan rate of cycling, revealing plausible correlations with mass transfer and electrode surface dynamics. Furthermore, the findings indicated that the selectivity towards HCOOH and C2H4 is closely related to the CO2/CO ratios of gas sources. This provides insight into the potential for modulating selectivity of industrial gas reduction for improved product quality and customization.